Biologically Inspired Optimization of Building District Heating Networks - Leiming Shang; Xiaomin Zhao (Institute of Advanced Engineering and Science, 2013)
In this paper we show that a biologically inspired model can be successfully applied to problems of building optimal district heating network. The model is based on physiological observations of the true slime mold Physarumpolycephalum, but can also be used for path-finding in the complicated networks of mazes and road maps. A strategy of optimally building heating distribution network was guided by the model and a well-tuned ant colony algorithm and genetic algorithm. The results indicate that although there are not large-scale efficiency savings to be made, the biologically inspired amoeboid movement model is capable of finding results of equal or better optimality than a comparable ant colony algorithm and genetic algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3890